A Probabilistic-Based Approach to Evaluate Winter Maintenance Vehicle Wash Water Management Options. (October 2016) - Miller, Christopher M.; Slaga, Joshua; Kennedy, Marla J.; Schneider, William H.
When locating new facilities, departments of transportation must consider how the wash water generated during routine winter operations will be managed. Previous research has shown that two options are likely to be the most cost-effective: (a) collecting and hauling off-site for disposal (CDISPOSE ) or (b) connecting to an existing sanitary sewer system (CSAN ). In this article, the cost-effectiveness of these two strategies for Ohio Department of Transportation (ODOT) maintenance facilities was evaluated probabilistically using Monte Carlo simulation. The probability CDISPOSE was the most cost-effective option was greater than 90% for existing ODOT facilities without sanitary sewer access if the sanitary sewer capital cost exceeded US$172, 000. Considering all ODOT facilities, there was 90% probability CDISPOSE was the most cost-effective option if the sanitary sewer capital cost exceeded US$280, 000. These results can be used to guide facilities management decisions regarding wash water management options for both existing and future facilities.